Conceptual Metaphor in Japanese Idiom with the Word Mizu ‘Water” - Nur Ainun; Mulyadi Mulyadi; Mhd. Pujiono (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
In Japanese, idioms are widely used to express feelings, ideas, and opinions. Idioms have a metaphorical meaning that contains the concept of Japanese people's thinking about something. This research examines the idiomatic forms of the word mizu based on the structure in Japanese. The research approach is qualitative. The research data are idioms which contain the word mizu with the kanji 「水」which sources from the Japanese idiom dictionary, the book 101 Japanese Idioms and online dictionaries. The analysis stage is to categorize idioms based on conceptual metaphor theory. Then, identify the metaphorical meaning by comparing the lexical meaning using a dictionary. Next, categorize and analyze the types of metaphors. Then, identify the image scheme that underlies the concept of water and interpret the concept of mizu in a conceptual metaphor. Finally, categorize the idioms contained in the data based on the classification of idiom forms. The results showed that based on structure, there were three classifications of the idiom form of the word mizu which consisted of 4 noun, 2 adjective, and 4 verb idioms. This means that the dominant idiom is closely related to everyday experience because most of the memory of human cognition is obtained from water as a source of life which shows that the mizu 'water' metaphor is dominant in the work and efforts of Japanese people who are known as hard workers. Keywords: Conceptual metaphor, Idioms, Mizu 'water', Japanese culture SARI Dalam bahasa Jepang, idiom banyak digunakan dalam mengungkapkan perasaan, gagasan, dan pendapat. Idiom memiliki makna metaforis yang berisi konsep berpikir masyarakat Jepang tentang sesuatu. Penelitian ini mengkaji bentuk-bentuk idiom dari kata mizu ‘air’ berdasarkan struktur dalam bahasa Jepang. penelitian ini merupakan Pendekatan penelitian adalah kualitatif. Data adalah idiom yang di dalamnya terdapat kata mizu dengan kanji 「水」yang bersumber dari kamus idiom Jepang, buku 101 Japanese Idioms dan kamus daring. Tahap analisis yang dilakukan adalah mengategorikan idiom berdasarkan teori metafora konseptual. Lalu, mengidentifikasi makna metaforis dengan cara membandingkan makna leksikal menggunakan kamus. Selanjutnya, mengategorikan dan menganalisis jenis metafora. Lalu, mengidentifikasi skema citra yang mendasari konsep air dan memaknai konsep mizu ‘air’ dalam metafora konseptual. Terakhir, mengategorikan idiom yang terdapat pada data berdasarkan klasifikasi bentuk idiom. Hasil penelitian menunjukkan bahwa berdasarkan strukturnya, terdapat tiga klasifikasi bentuk idiom kata mizu yang terdiri dari 4 idiom nomina, 2 idiom adjektiva, dan 4 idiom verba. Hal ini berarti Idiom yang mendominasi erat kaitannya dengan pengalaman sehari-hari karena sebagian besar memori kognisi manusia didapat dari air sebagai sumber kehidupan yang menunjukkan bahwa metafora mizu ‘air’ dominan pada pekerjaan dan usaha orang-orang Jepang yang dikenal sebagai pekerja keras. Kata kunci: Metafora konseptual, Idiom, Mizu ‘air’, Budaya jepang